2017
DOI: 10.1097/iae.0000000000001315
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinographic and Visual-Evoked Potential Changes in Relation to Chelation Modality in Children With Thalassemia

Abstract: Preclinical electrophysiologic changes existed in thalassemics, more obvious in those on deferoxamine. Electrophysiologic studies analysis denotes an early toxic macular insult rather than optic nerve affection. Thus, regular follow-up using multifocal electroretinogram and pattern electroretinogram is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Prior studies have evaluated electrophysiologic changes of iron chelation therapy in asymptomatic patients who lacked apparent fundoscopic findings, noting decreased amplitudes compared with controls. 7 Therefore, mfERG may provide a sensitive early diagnostic test for patients with suspected toxicity. 7,9 Management of iron chelator toxicity involves multidisciplinary decision making and weighing the risks and benefits of continued therapy with the need to prevent morbidity and mortality from iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have evaluated electrophysiologic changes of iron chelation therapy in asymptomatic patients who lacked apparent fundoscopic findings, noting decreased amplitudes compared with controls. 7 Therefore, mfERG may provide a sensitive early diagnostic test for patients with suspected toxicity. 7,9 Management of iron chelator toxicity involves multidisciplinary decision making and weighing the risks and benefits of continued therapy with the need to prevent morbidity and mortality from iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…That study also found that DFO was more toxic to the macula than oral chelators like DFX. 21 Taneja et al 22 observed ocular changes caused by the different treatment regimens recommended for patients with TM over the course of a year and reported that changes occurred in proportion to the increase in serum ferritin levels. Similarly, Cennamo et al 23 reported, in a study that used OCTA to evaluate vascular changes in retinal and choriocapillaris perfusion, that high serum ferritin levels in TM patients may be significantly associated with choriocapillary hypoperfusion, but Kazancı et al 10 reported that there was no relationship between ferritin levels and ocular changes when comparing TM patients with a control group in a study that also evaluated vascular parameters using OCTA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been reported that visual evoked potential values are altered from the normal range in beta-thalassemic individuals due to iron overload and on the other hand neurotoxicity due to DFO is another culprit which causes disrupted visual evoked potential [24][25][27][28] according to some reports.…”
Section: Visual Evoked Potentials (Vep)mentioning
confidence: 99%